Pedagogický dualizmus teoretického a praktického: historické pozadie a súčasné ilúzie. Pedagogical dualism of theory and practice: historic background and current illusions. - Višňovský Emil; Kaščák Ondrej; Pupala Branislav (Czech Pedagogical Society, 2012)
The paper newly raises the traditional question of educational science - the question of the relationship between theoretical knowledge and practice, between science and practice. This target problem is discussed using a complex theoretical overview and integrating this problem of educational science into broader context of development of social sciences and humanities. Using this umbrella, transformations of relationship between theory and practice, discussed from the period of Classical Antiquity, through Modern period until present times, are interpreted. Consequently,transformations of relationship between theory and practice in this timeline provide a background for explaining the oscillation of self-representation of educational science as either theoretical or practical science. Finally, the well-known concept of teacher as reflective practitioner announced in the field of teacher training asa promising example of how to definitely bridge the gap between academic knowledge and knowledge necessary for practical execution of education is elaborated on.